Crisis de la universidad en el Perú: un problema de su naturaleza e identidad - Arias Gallegos, Walter Lizandro (2013)
In this article, there is a reflection about the identity of CatholicUniversities from its nature as an eminently academic institution andthe crisis that is sent to the higher education of university level.The historic aspects, research functions, teaching, university extensionare reviewed, as well as the university education problems thatcomprise the poor academic production, deficient education, its limitedconnection with the reality of the country and little clarity on thefunctions of university teachers and their students.